PERAN WORK LIFE BALANCE DALAM MEMEDIASI KEPEMIMPINANTRANSFORMASIONAL TERHADAP EMPLOYEE ENGAGEMENTDI PT. PUPUK KUJANG CIKAMPEK (Jurnal Psikologi Udayana, 2026)
Employee engagement is the extent to which people enjoy their work, trust it, and feel appreciated. This research aims to find out the role of work life balance in mediating transformational leadership on employee engagement. using a correlational quantitative method with a total of 191 PT employees as respondents. Cikampek Kujang Fertilizer selected by convenience. Data was collected using 3 scales, namely, the Development Dimensions International Inc (DDI) scale, the Global Transformational Leadership (GTL) scale and the Work Life Balance (WLB) scale. Researchers found that work life balance can mediate the influence of transformational leadership on employee engagement by 92.7% with an estimated value of 0.262, (p